2020
DOI: 10.5624/isd.2020.50.3.209
|View full text |Cite
|
Sign up to set email alerts
|

Discriminatory ability of cervical vertebral maturation stages in predicting attainment of the legal age threshold of 14 years: A pilot study using lateral cephalograms

Abstract: Purpose: In India, the age of 14 years is the legal age threshold for child labour. Therefore, in suspected instances of child labour, age assessment plays a crucial role in determining whether a violation of the law on the employment of children has occurred. The aim of this retrospective cross-sectional study was to assess the discriminatory ability of stages of cervical vertebral maturation (CVM) in predicting the legal age threshold of 14 years. Materials and Methods: Routinely taken lateral cephalograms f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Individuals who are illegal or have lost their legal status can be examined to estimate their chronological age using CVM. At around 15-16 years of age, the somatic pattern of cervical vertebral growth reaches its final maturation, with the greatest cervical vertebral growth rate occurring between 10 and 12 years (30,31). However, a few studies have shown that the use of a single variable, such as CVM, is unreliable in estimating age.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who are illegal or have lost their legal status can be examined to estimate their chronological age using CVM. At around 15-16 years of age, the somatic pattern of cervical vertebral growth reaches its final maturation, with the greatest cervical vertebral growth rate occurring between 10 and 12 years (30,31). However, a few studies have shown that the use of a single variable, such as CVM, is unreliable in estimating age.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, younger patients within the stage 1 period will require further delineation by adjunctive skeletal maturation assessment methods such as the commonly employed radiographic analysis of hand-wrist ossification, 17 or less frequently commissioned radiographic evaluations of proximal humerus ossification or cone-beam CT of the cervical vertebrae. 17,[40][41][42] Furthermore, objective evaluation of success of surgery was not completed. Such objective measures, including extent of surgical correction achieved, patient satisfaction, and deformity recurrence rates, are essential to consider in the debate regarding optimal timing for SCOPE.…”
Section: Limitationsmentioning
confidence: 99%